COMPARISON OF TWO TURNING REGIMENS (1 VERSUS EVERY 2 HOURS) IN THE PREVENTION OF CONSTIPATION IN PATIENTS WITH STROKE - Nur Hidayati; Tintin Sukartini; Padoli Padoli (Belitung Nursing Journal, 2019)
Background: Constipation is one of the most common problems in stroke due to inactivity and immobility. Objective: To compare one hour and every two-hour turning regimens in the prevention of constipation in patients with stroke. Methods: This was a quasi-experimental research with pretest posttest with control group design. There were 39 participants assigned in intervention group (n=17) and control group (n=22). The intervention group turned every one hour, while control group turned every two hours. The turning regimen was implemented for five days. A bowel score was used to measure constipation. McNemar Test and Fisher Test were used to measure and compare the bowel score between the two groups. Results: There was no significant difference in the effect of two turning regiments on constipation (p > .05). However, based on a descriptive result, there was a slight decrease in the number of constipation from 47% to 29.4% in the intervention group, and from 32% to 27% in the control group. Conclusion: Turning might still become an effective way to prevent constipation in patients with stroke either every one hour or two hours without diet modification.